저글루테린 및 저아밀로스 중생종 기능성 벼 ‘건양2호’ - 이종희(Jong-Hee Lee); 이지윤(Ji-Yoon Lee); 송유천(You-Chun Song); 여운상(Un-Sang Yeo); 박노봉(No-Bong Park); 김춘송(Choon-Song Kim); 손영보(Young-Bo Sohn); 박동수(Dong-Soo Park); 한상익(Sang-Ik Han); 김상열(Sang-Yeol Kim); 김우재(Woo-Jae Kim); 최대식(Dae-Sik Choi); et al. (Korean journal of breeding, 2015)
저글루테린 및 저아밀로스 품종인 ‘건양2호’는 ‘중국173 호’와 ‘주남벼’를 각각 모본과 부본으로 인공교배 후 집단육 종법을 통하여 육성한 기능성 품종이다. ‘건양2호’의 출수기 는 영호남 및 중부평야지 보통기 보비재배에서 8월 10일로 ‘남평벼’보다 5일 빠른 중생종이다. 간장은 65 cm로 내도복 성이며, 불시출수와 수발아는 안되는 편이고 내냉성은 ‘남평 벼’와 비슷한 편이다. 잎도열병 밭못자리검정에서 중정도 저항성을 보였으며, 줄무늬잎마름병과 흰잎마름병(K1, K2, K3) 에는 저항성이다. ‘건양2호’의 아밀로스함량은 11.5%로 메벼 와 찹쌀의 중간형태로 불투명한 저아밀로스 품종이며, 단백질 함량은 6.0%로 ‘남평벼’보다 약간 낮으며 소화성 전분인 글 루테린 비율이 63.1%로 ‘남평벼’의 73.8%보다 낮다. ‘건양2 호’의 쌀 수량성은 4.61 MT/ha로 ‘남평벼’보다 9% 감수되었 고, 적응지역은 영호남 및 중부 평야 1모작지이다(품종 등록 번호: 제5105호). In chronic renal failure, to reduce the burden on the kidneys, it is necessary to provide patients with therapy based on a low-protein diet. To cope with this situation, low and easy to-digest protein rice variety is helpful. ‘Geongyang2’, low glutelins rice cultivar, was developed by the National Institute of Crop Science (NICS), RDA, Miryang, Korea in 2012. ‘Geongyang2’was derived from a cross between ‘Junambyeo’and‘Chugoku 173’ as a source of low glutelin and amylose. The pedigree of ‘Geongyang2’was YR24174-B-B-B-B-46 and designated as the ‘Milyang262’ in 2009. The local adaptability test of ‘Milyang262’ was carried out at six locations from 2010 to 2012. ‘Geongyang2’ is a mid-maturing ecotype with 65cm in culm length and the number of spikelet/panicle and 1,000 grain weight of brown rice were slightly lower compared to those of ‘Nampyeongbyeo’. ‘Geongyang2’ is resistant to bacterial blight and virus disease while susceptible to major insect and pest. The glutelin and amylose contents of ‘Geongyang2’ were 63.1% and 11.5%, respectively. The milled rice yield of ‘Gyeongyang2’ is 4.61MT/ha at the ordinary transplanting of the local adaptability test. This cultivar would be adaptable to the plain paddy field of middle, honam and yeongnam province of Korea under ordinary cropping system.